Pelatihan Penyusunan RPP dan Modul Proyek P5 Digital Terintegrasi Kurikulum Merdeka: Upaya Mendukung Sekolah Adiwiyata Mandiri - Rahayu, Ayu; Nasir, Agus; Sopiandy, Dede; Puspitasari, Serli; Fiqran, Fiqhi Al (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Sustainable education is one of the main pillars in facing global challenges such as environmental degradation and climate change. The Adiwiyata program, initiated by the Indonesian government, aims to integrate environmental values into the school curriculum, helping students not only understand environmental concepts theoretically, but also apply them in everyday life. SMPN 1 Kolaka, as a community service partner, is working to achieve the Adiwiyata Mandiri award and needs strengthening in the implementation of the Adiwiyata concept, especially in the preparation of learning tools based on environmental values. The training program includes five main stages, namely the planning, implementation, technology application, mentoring, evaluation, and program sustainability stages. In the training process, teachers are invited to be more skilled in preparing Learning Implementation Plans (RPP) and Project Modules for Strengthening the Pancasila Student Profile (P5) which are integrated with environmental values. The results of this training showed a significant improvement in teachers' abilities, as evidenced by the difference in pretest and posttest scores by 20%. In addition, feedback from participants showed that this activity received positive appreciation, with a satisfaction rate of 90%. The success of this training not only improves teachers' competence in developing environment-based learning, but also strengthens teachers' capacity in developing environment-based learning.